Hand Hygiene Compliance in the Setting of Trauma Resuscitation. Issue 1 (January 2017) - Haac, Bryce; Rock, Clare; Harris, Anthony D.; Pineles, Lisa; Stein, Deborah; Scalea, Thomas; Hu, Peter; Hagegeorge, George; Liang, Stephen Y.; Thom, Kerri A.; ,
Abstract: Introduction: Healthcare-associated infections are a significant health burden, and hand hygiene (HH) is an essential prevention strategy. World Health Organization (WHO) 2009 guidelines recommend washing hands during five moments of patient care; 1)before touching a patient; 2)before a clean procedure; 3)after body fluid exposure; and 4)after touching a patient or 5)patient surroundings. HH opportunities at these 5 moments are frequent and compliance is low (22-60%). Infection risk is particularly high in trauma patients, and HH compliance during active trauma resuscitation has yet to be evaluated. Materials and Methods: Using video surveillance, all healthcare worker (HCW)-patient interactions for 30 patients were retrospectively reviewed for HH compliance according to WHO guidelines and glove use during initial resuscitation at a level-1 trauma center. Results: 342 HCW-patient interactions and 1034 HH opportunities were observed. HH compliance with the WHO moments was 7% (71/1034) overall; 3% (10/375) before patient contact, 0% (0/178) before a clean procedure, 11% (2/19) after body fluid contact, 15% (57/376) after patient contact and 2% (2/86) after contact with the environment. Glove use was more common, particularly before (69%) and after (47%) patient contact and after body fluid contact (58%). No HH was observed before clean procedures, but HCW donned new gloves 75% of the time before bedside procedures. If donning/removing gloves was included with HH as compliant, compliance was 57% overall. Conclusion: HH opportunities are frequent and compliance with WHO HH guidelines may be infeasible, requiring significant amounts of time that may be better spent with the patient during the golden hour of trauma resuscitation. In an era where more scrutiny is being applied to patient safety, particularly the prevention of inpatient infections, more research is needed to identify alternative strategies (e.g. glove use, prioritizing moments) that may more effectively promote compliance in this setting.